TASRIH MAHMOUD ABBAS HAULA NAZ’I SILAHI AL-MUQAWAMAH: MANDZHUR TAHLIL AL-KHITAB AN-NAQDIY - Muhammad Aqil Wahid; Abdul Muid; Gamzat Dibirov (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2025)
Talk of disarming the resistance has, of late, risen to the surface of the international public dialectic. The purpose of this study is to identify and describe the instruments used by Mahmoud Abbas in propagating the discourse of disarming the resistance in the text dimension, the discourse praxis dimension and the socio-cultural praxis dimension. This research uses a qualitative descriptive approach. The data in this study come from Mahmoud Abbas' speeches spread in the mass media from year to year. The data was collected using reading and note-taking techniques. Data analysis was conducted using Norman Fairclough's critical discourse analysis method, which consists of three dimensions: text dimension, discourse praxis dimension and situational praxis dimension. The results are the findings of three dimensions: text dimension, discourse praxis dimension and situational praxis dimension. The Findings are Abbas' polarization of the public to support the discourse of disarmament and demonization of Hamas through the use of instruments such as: representation of the perpetrator through lexical choices made by using insults or giving official names. In addition, Abbas produces disarmament discourses by using accusations against Hamas and utilizing his political position to legitimize his propaganda.